HUBUNGAN KADAR hsCRP DAN FUNGSI KOGNITIF PASCA STROKE ISKEMIK - Yuliarni Syafrita (NEURONA, 2013)
INTRODUCTION THE INCIDENCE OF COGNITIVE IMPAIRMENT AFTER ISCHEMIC STROKE IS HIGH HIGH LEVELS OF HIGH SENSITIVECREACTIVE PROTEIN HSCRP ARE ASSOCIATED WITH COGNITIVE IMPAIRMENT SEVERAL POPULATIONBASED STUDIES REPORTED AN ASSOCIATION BETWEEN HSCRP LEVEL AND COGNITIVE DECLINE BUT THERE WAS LACK EVIDENCE OF ASSOCIATION OFACUTE PHASESTROKE HSCRP LEVEL WITH COGNITIVE IMPAIRMENT AFTER STROKE INCIDENCE